IDENTIFIKASI KANDUNGAN BORAKS PADA MI BASAH DI PASAR TRADISIONAL KOTA BENGKULU - Widelia, Putri; Farizal, Jon; Narti, Mula (Journal of Nursing and Public Health, 2018)
Background: Wet noodles (raw wet noodles or wet noodles) are one of a kind of noodles that are widely known and favored by Indonesian. The use of borax is still high based on POM Bengkulu. Indonesia ranks is second after korea. The wet noodle industry is widespread in many parts of Indonesia and is mostly produced by home industries, and small or medium industries. The use of this borax in foods because boric acid can inhibit the growth of microorganisms, so the food has been added borax looks fresh and durable lasting. This study aims to identify the presence or absence of borax in wet noodles in the city of Bengkulu 2017.Research Objectives: To identify at least the wet noodle slippers sold in traditional Bengkulu City 2017.Method: This research method is qualitative test of kurkuma paper test method, the sample in this research is 33 wet noodles sold in traditional market of Bengkulu City with sampling technique of simplerandom sampling.Result: Result of research from 33 wet noodles sold in traditional market of Bengkulu City, found most of 22 (66,66%) wet noodle containing borax. In the kurkuma method, a positive sample contains borax, with reddish brown or red brick. The characteristics of wet noodles that contain borax texture is chewy, more shiny, not sticky, and not quickly broken.Conclusion: Most (66.66%) found the borax on wet noodles sold in traditional markets of Bengkulu City. So it is necessary to socialize from Dinkes to traders about the danger of borax, and can minimize the use of borax by wet noodle traders.